Role And Impact Of The Packaging Effect On Consumer Buying Behaviour (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The marketing activities are based some of the special character, these kind of character are to be followed and prepared for the purpose of identifying their product. Producer needs the something new in their product; the product must to have some new ideas and identity form the other product. The entire marketing world is based on product using in their personal life of the individual one. Family are the decision maker in the usage of the new product or the old one available in the marketing area. The coverage of the marketing field in the product to be followed in future also, every producer of the product to find a new way to promote their business in the forward way. This article contains the scope, objectives and limitations of the study and the Chi-square test to compare the data details to the customers effectiveness related for the new policy.